The Central Autonomic Network and Regulation of Bladder Function - Roy, Holly Ann; Green, Alexander L. (Frontiers in Neuroscience, 2019)
The autonomic nervous system (ANS) is involved in the regulation of physiologic and homeostatic parameters relating particularly to the visceral organs and the co-ordination of physiological responses to threat. Blood pressure and heart rate, respiration, pupillomotor reactivity, sexual function, gastrointestinal secretions and motility, and urine storage and micturition are all under a degree of autonomic nervous system control. Furthermore, there is close integration between the autonomic nervous system and other neural functions such as emotion and cognition, and thus brain regions that are known to be important for autonomic control are also implicated in emotional functions. In this review we explore the role of the central autonomic nervous system in the control of the bladder, and the implications of this for bladder dysfunction in diseases of the autonomic nervous system.